Up-regulation of adenylylcyclases I and II induced by long-term adaptation of rats to morphine fades away 20 days after morphine withdrawal - Ujcikova, Hana; Dlouha, Katerina; Roubalova, Lenka; Vosahlikova, Miroslava; Kagan, Dmytro; Svoboda, Petr (Biochimica et biophysica acta, 2011)
BACKGROUND: Activation of adenylyl cyclase (AC) by prolonged exposure of mammalian organism to morphine was demonstrated in previous studies of mechanism of action of this drug. However, expression level of individual AC isoforms was not analyzed in crucial cell structure, plasma membrane (PM). METHODS: Rats were adapted to morphine for 10 days and sacrificed 24h (group+M10) or 20 days (+M10/-M20) after the last dose. Control animals were sacrificed in parallel with morphine-treated (groups-M10 and (-M10/-M20)). Percoll®-purified PM were isolated from brain cortex and analyzed by immunoblotting and specific radioligand binding. RESULTS: ACI (ACII) was increased 8× (2.5×) in morphine-adapted rats (+M10) when compared with controls (-M10). Increase of ACI and II by long-term adaptation to increasing doses of morphine represented a specific effect as the amount of ACIII-ACIX, of prototypical PM marker, Na, K-ATPase and of trimeric G protein α and β subunits was unchanged. Increase of ACI and II was not detected in PM isolated from group (+M10/-M20). Thus, the marked increase of ACI and ACII faded away 20 days since the last dose of morphine. CONCLUSIONS: We assume that the specific increase in expression level of ACI and ACII in brain cortex of morphine-adapted rats proceeds as a compensatory, homeostatic response to prolonged exposure to inhibitory drug, morphine. GENERAL SIGNIFICANCE: Our findings demonstrate that the dramatic and specific change of the crucial component of the opioid receptor cascade in brain cortex, manifested as an increase in PM level of ACI and II, is reversible.
Keywords: elektroforéza v polyakrylamidovém gelu; Rats; Up-Regulation; upregulace; Rats, Wistar; mužské pohlaví; receptory opiátové delta; sodíko-draslíková ATPasa; morfin; krysa rodu Rattus; adenylátcyklasy; Electrophoresis, Polyacrylamide Gel; Isoenzymes; zvířata; izoenzymy; abstinenční syndrom; Adenylyl Cyclases; potkani Wistar; Receptors, Opioid, delta; Morphine; Sodium-Potassium-Exchanging ATPase; Substance Withdrawal Syndrome; Male; Animals